Publication Trends on Mitophagy in the World and China: A 16-Year Bibliometric Analysis - Chen, Jingli; Li, Xin; Jia, Yifan; Xia, Zhongyuan; Ye, Jishi (Frontiers in Cell and Developmental Biology, 2021)
In the past 16 years, research on mitophagy has increasingly expanded to a wider range of subjects. Therefore, comprehensively analyzing the relevant progress and development trends on mitophagy research requires specific methods. To assess the hotspots, directions, and quality of results in this field worldwide, we used multiple tools to examine research progress and growing trends in research on the matter during the last 16 years (from 2005 to 2020). We also compared the quantity and quality of the literature records on mitophagy published by research institutions in China and other developed countries, reviewed China's contribution, and examined the gap between China and these developed countries. According to the results of our bibliometric analysis, the United States and its research institutes published the most papers. We identified cell biology as the most commonly researched subject on mitophagy and AUTOPHAGY as the most popular journal for research on mitophagy. We also listed the most cited documents from around the world and China. With gradually increased funding, China is progressively becoming prominent in the field of mitophagy; nevertheless, the gap between her and major countries in the world must be closed.